2009
DOI: 10.1111/j.1523-1739.2008.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Leadership: a New Frontier in Conservation Science

Abstract: Leadership is a critical tool for expanding the influence of conservation science, but recent advances in leadership concepts and practice remain underutilized by conservation scientists. Furthermore, an explicit conceptual foundation and definition of leadership in conservation science are not available in the literature. Here we drew on our diverse leadership experiences, our reading of leadership literature, and discussions with selected conservation science leaders to define conservation-science leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 27 publications
1
103
0
Order By: Relevance
“…In one of the first articles, published in 2004, the authors cited a total of five sources, none of which referenced any of the abundant research about leadership from the previous decades. In 2008, Conservation Biology published an article in which researchers reported that a search of articles in Web of Science using the search terms "conservation biology OR conservation science AND leadership" produced 22 articles, most of which, they noted, did not actually apply to leadership (Manolis et al 2008). Six years later, I conducted the same search and found 60 articles, and similarly, most were not actually relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the first articles, published in 2004, the authors cited a total of five sources, none of which referenced any of the abundant research about leadership from the previous decades. In 2008, Conservation Biology published an article in which researchers reported that a search of articles in Web of Science using the search terms "conservation biology OR conservation science AND leadership" produced 22 articles, most of which, they noted, did not actually apply to leadership (Manolis et al 2008). Six years later, I conducted the same search and found 60 articles, and similarly, most were not actually relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Even though leadership is a universal phenomenon, its magnitude of difficulty of inducing changes is still affected by the organizations and cultures in which it appears (Bass, 1997; Manolis et al, 2009), whereby conservation interventions question the need for changes in human behaviour (Mascia et al, 2003;Balmford & Cowling, 2006). In the EMCs, the challenges for leadership in forestlands conservation are numerous.…”
Section: Discussionmentioning
confidence: 99%
“…Leaders must therefore be able to develop and maintain the operational efficiency and resilience of their organizations through building appropriate organizational structures, strategies, accountability and finances. Despite the acknowledged role of leadership in conservation, the sector has been relatively slow to adopt evidence-based models of good leadership practices from other sectors (Manolis et al, 2009). There have been attempts to bring greater clarity and definition to what is actually meant by leadership in various conservation contexts (Bruyere, 2015).…”
Section: Thematic Area 3: Effective Leadership and Strong Organizationsmentioning
confidence: 99%